Using the amihud illiquidity ratio to optimize a quantitative investment strategy - Hesse, Rouven Leon (2022)
This research explored whether the performance of investment strategies based on liquidity can be enhanced by combining liquidity with size and optimizing the cut-off levels for liquidity quantiles. The Amihud (2002) illiquidity ratio is the underlying liquidity measure used for the analysis. In the in-sample period the strategy investing in the 10% of the stocks with the lowest liquidity in the S&P500 achieved the highest risk adjusted return. The results found in the in sample period cannot be replicated in the out-of-sample period.